Additive Manufacturing of Piezoelectric Niobium-Doped Lead Zirconate Titanate (PZT-N) by Binder Jetting - Marco Mariani; Elisa Mercadelli; Laura Cangini; Carlo Baldisserri; Carmen Galassi; Claudio Capiani; Nora Lecis (Crystals, 2023)
Binder jetting is an emerging indirect additive manufacturing technique for ceramic materials, which could be employed to produce application-oriented designed components impossible to achieve with traditional processes and featuring enhanced performances. In our study, niobium-doped lead zirconate titanate (PZT-N) powder, usually processed through the standard press-and-sinter route, was employed as the raw material. First, the powder was characterized in terms of granulometry and flowability to assess its suitability for the printing process. Then, shaping by binder jetting was studied, and the effect of three levels of binder saturation (75–90–105%) on the green bodies was assessed. Finally, the microstructure of the sintered samples was studied using SEM, to investigate the effect of thermal treatments on the grain size distribution and residual porosity (~40%). The piezoelectric properties were measured and compared to those of conventionally processed material. The piezoelectric charge and voltage constants (d33 and g33) were evaluated to determine the possible use of printed parts as porous piezoelectric components to be exploited in hydrophones in the direct mode.